Analysis of Human Resource Policy in Improving The Quality of Employee Performance in The Department of Population Control, Women's Empowerment and Child Protection of Gunungsitoli City - Trima Putri Harefa; Odaligoziduhu Halawa; Syah Abadi Mendrofa; Fatolosa Hulu (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze human resource policies to improve the quality of employee performance at the Population Control, Women's Empowerment, and Child Protection Service of Gunungsitoli City. The research focuses on three main objectives: (1) to determine the form of human resource policies implemented to improve performance quality, (2) to identify supporting and inhibiting factors in the implementation of these policies, and (3) to formulate appropriate strategies to improve employee performance. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that the implemented human resource policies include training and competency development, performance assessment based on work indicators, and a reward system and work discipline. Supporting factors for the implementation of these policies include leadership support, active employee participation, and the availability of a training budget. However, there are also inhibiting factors such as a lack of professional human resources, limited supporting facilities and infrastructure, and low work motivation among some employees. The strategies implemented to improve performance quality include strengthening supervision, developing a collaborative work culture, improving the quality of training, and regular evaluation of policy implementation. This study concludes that appropriate and consistent human resource policies play a crucial role in building more optimal employee performance within the service environment.